Does Locality Make a Difference? Assessing the Effectiveness of Location-aware Narratives - Karapanos, Evangelos; Barreto, Mary L.; Nisi, Valentina; Niforatos, Evangelos (My University, 2012)
With the increasing sophistication of mobile computing, a growing interest has been paid to locative media that aim at providing immersive experiences. Location aware narratives are a particular kind of locative media that aim at "telling stories that unfold in real space". This paper presents a study that aimed at assessing an underlying hypothesis of location-aware narratives: that the coupling between the physical space and the narrative will result in increased levels of immersion in the narrative. Forty-five individuals experienced a location-aware video narrative in three locations: (a) the original location that contains physical cues from the narrative world, (b) a different location that yet portrays a similar atmosphere, and (c) a location that contains neither physical cues nor a similar atmosphere. Significant differences were found in users' experiences with the narrative in terms of immersion in the story and mental imagery, but not with regard to feelings of presence, emotional involvement or the memorability of story elements. We reflect on these findings and the implications for the design of location-aware narratives and highlight questions for further research.
Keywords: Location-aware narratives; Locative media; Narrative transportation; Presence